Ethical Considerations in AI-Powered Student Profiling for Personalized Learning (Journal of Informatics Education and Research, 2024)
The rapid incorporation of AI in education has led to the development of AI-generated student profiles that facilitate personalised learning. Although these technologies enable personalised instruction and improved student outcomes, they also present significant ethical concerns. This research investigates the ethical implications of AI-powered student profiling, including the dangers associated with reliance on educational technology, transparency, consent, bias, and data privacy. It also discusses the dangers of stereotyping, the influence of profiling on the autonomy of students, and the responsibility of schools to establish inclusive classrooms for all students. The objective of this research is to provide educators, legislators, and AI developers with a framework for addressing the challenges associated with the responsible implementation of AI in education, while simultaneously promoting innovation and maintaining ethical standards.